2000
DOI: 10.1002/1096-9861(20000821)424:2<307::aid-cne9>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor inhibits cell proliferation in cultured avian inner ear sensory epithelia

Abstract: Postembryonic production of inner ear hair cells occurs after insult in nonmammalian vertebrates. Recent studies suggest that the fibroblast family of growth factors may play a role in stimulating cell proliferation in mature inner ear sensory epithelium. Effects of acidic fibroblast growth factor (FGF-1) and basic fibroblast growth factor (FGF-2) were tested on progenitor cell division in cultured auditory and vestibular sensory epithelia taken from posthatch chickens. The effects of heparin, a glycosaminogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 149 publications
(240 reference statements)
3
29
0
Order By: Relevance
“…The rapid downregulation of Fgf signaling is in accordance with findings in chicken sensory epithelia, in which Fgfr3 is highly expressed in support cells but is down-regulated rapidly after hair cell death (62). Additionally, in the chicken down-regulation of Fgf signaling is required for regeneration to occur, because the addition of Fgf inhibits support cell division after damage (63).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The rapid downregulation of Fgf signaling is in accordance with findings in chicken sensory epithelia, in which Fgfr3 is highly expressed in support cells but is down-regulated rapidly after hair cell death (62). Additionally, in the chicken down-regulation of Fgf signaling is required for regeneration to occur, because the addition of Fgf inhibits support cell division after damage (63).…”
Section: Resultssupporting
confidence: 84%
“…Therefore, it is possible that Cdk inhibitors are regulated by as yet unidentified, Notchindependent signals. Possibly, Fgf signaling inhibits proliferation, as demonstrated in the chicken inner ear (63).…”
Section: The Regulation Of Notch Signaling In Combination With Mitogementioning
confidence: 99%
“…Which extracellular factors might alter these signaling pathways? Addition of basic FGF (bFGF) to cultured cochlear ducts leads to decreased SC division (Oesterle et al, 2000). Consistent with this, expression of FGF receptor3 is abundant in quiescent SCs of the BP and becomes highly decreased in areas where numerous SCs are dividing, suggesting that attenuated signaling through this receptor must occur before SC re-entry into the cell cycle (Bermingham-McDonogh et al, 2001).…”
Section: Signals Regulating Sc Divisionmentioning
confidence: 88%
“…Consistent with this, expression of FGF receptor3 is abundant in quiescent SCs of the BP and becomes highly decreased in areas where numerous SCs are dividing, suggesting that attenuated signaling through this receptor must occur before SC re-entry into the cell cycle (Bermingham-McDonogh et al, 2001). In the avian vestibular epithelium, in vitro experiments demonstrate SC proliferation is inhibited by bFGF (Oesterle et al, 2000), Retinoic Acid (Warchol, 2002), N cadherin (Warchol, 2006) and Dexamethasone (Warchol, 1999). In contrast, Insulin, Insulin-like Growth Factor 1, Transforming Growth Factor alpha and Tumor Necrosis Factor alpha have mitogenic effects on vestibular SCs, as does the extracellular matrix molecule, Fibronectin (Oesterle et al, 1997;Warchol, 2002).…”
Section: Signals Regulating Sc Divisionmentioning
confidence: 99%
“…Results of cell and organ culture studies of the avian ear suggest that vestibular supporting cells produce endogenous mitogens that stimulate proliferation in an autocrine or paracrine fashion (Warchol and Corwin, 1993;Warchol, 1995). The speciWc mitogen(s) have not been identiWed, but other culture studies have shown that the proliferation of these cells can be modulated by treatment with IGF-1 and FGF2 (Oesterle and Hume, 1999;Oesterle et al, 1997Oesterle et al, , 2000 and certain immune cytokines (Warchol, 1999). Unfortunately, the role of any of these factors in the regenerative process in vivo has not been demonstrated.…”
Section: Growth Factors and Receptorsmentioning
confidence: 99%